Investigating the role of dithiophosphate in the flotation of base metal sulfides - Jordaan,Thomas Ignatius (Department of Chemical Engineering, 2019)
The behaviour of sodium diethyl dithiophosphate (SEDTP) in flotation systems is of major interest to the Platinum Group Mineral (PGM) and Base Metal Sulphide (BMS) industry. Operationally, SEDTP has proved to be a point of contention as there are conflicting views regarding the role of collector with regard to its behaviour at the air-water and solid-water interface in the flotation process. The main objective of this thesis is to attempt to elucidate the surfactant behaviour of SEDTP and in particular its role at both the air-water and solidwater interface. To interpret its behaviour at the air-water interface, bubble pressure tensiometry was used to investigate the effect that SEDTP had on equilibrium surface tension. This was compared to the surface tension of a polypropylene glycol (PPG) frother, which was selected as a benchmark due to it being a surface active agent at the air-water interface and its general use in the industry as a frother. One of the most common collectors used in the PGM industry, sodium ethyl xanthate (SEX), was used as a benchmark collector, which is not known to affect the surface tension. Reagent concentrations were pushed high enough for the air-water surfactant, the frother, to reduce the surface tension (5-100 mM). The maximum concentrations of the three different reagents were tested at pH 7, 9 and 11. The pH was kept constant for other experiments at pH 9 and throughout the investigation the make-up water was deionized water (DIW). To investigate SEDTP’s behaviour at the air-water interface, a frothing column was used to determine its effect on foam stability. Reagent dosages used were similar to those used on plant operations, which are much lower than those used in surface tension experiments. Foam stability experiments were carried out at pH 9 using synthetic plant water (SPW) the constitution of which is shown in the thesis. Solids were subsequently introduced to investigate the effect that SEDTP had on froth stability (3-phase) and compare it to foam stability (2- phase). The solids used were samples from a PGM-containing silicate ore, milled to 60% passing 75 micron. As with the foam stability investigation, the froth stability experiments were carried out at pH 9. The pulp phase floatability of pyrite and galena with SEDTP was measured to investigate the effect that SEDTP had on particle hydrophobicity. Collector-less and pure reagent flotation recoveries were established to relate the effect that reagents had on the floatability. The microflotation of pyrite was carried out at pH 4 and pH 9 to investigate the effect of pH on the flotation of pyrite when using either SEDTP or SEX as single reagents and in the presence of a PPG frother. The effect of frother type and chain length in a mixture containing SEDTP was also investigated on pyrite at pH 4. Microflotation of galena was done at pH 4 to test the relative effect of SEDTP either as a single reagent or in conjunction with a frother compared to pyrite at the same conditions. Collector dosages for all microflotation experiments were determined so as achieve 50% of a single monolayer surface coverage on the mineral surface. This was done by determining the BET surface area of the mineral and using the known surface area footprint of a single collector molecule. Frother concentrations were similar to those used in previous studies. Furthermore, to minimize surface oxidation of the minerals, the samples were stored in nitrogen in a desiccator and acid-washed prior to the experiments. SPW was used to simulate a plant-like solution. Equilibrium surface tension results showed that the reagents used reduced the surface tension in the order: PPG frother, SEDTP, SEX. This is ascribed to the role of these reagents when adsorbing at the air-water interface. Foam stability tests were shown to be more sensitive than surface tension measurements in predicting the surface activity of SEDTP at much lower concentrations than the concentrations used for surface tension experiments. SEDTP did not have any significant effect on foam stability when used as a single reagent. However, when combined with a frother there was a significant improvement in the foam stability. SEX did not display any foam stabilizing effect with either a frother or in a collector mixture with a frother. This is consistent with the surface tension results, thus indicating that, compared to SEX, SEDTP has surface active properties, and more so when in the presence of a frother. The presence of solids in the froth stability experiments diminished the role of SEDTP at the air-water interface since no froth stabilizing effect was observed when it was combined with a frother compared to the two-phase foam system. This may be due to SEDTP partially adsorbing on the solid particles (as was shown by UV-Vis experiments) and thus not being available to affect the air-water interface. The collector mixture containing SEDTP and SEX decreased the froth stability. This may be attributed to increased particle hydrophobicity upon the addition of a collector, which could lend to the destabilization of the froth. Microflotation mineral recoveries are indicative of the bubble-particle attachment efficiency and hydrophobicity. At pH 9, no single reagents improved the recovery of pyrite. Combining SEDTP with a frother did, however, improve the recovery significantly. This was not observed for SEX as a single reagent or when combining SEX with a frother. However a 90 SEDTP: 10 SEX collector mixture containing frother exhibited further synergy by improving the total recovery and flotation rate of pyrite. At pH 4, single reagent flotation improved reagent-less flotation in all cases. The more acidic conditions would give rise to a more reducing environment which accommodates adsorption of surfactants at the solid-water interface. A 90 SEDTP: 10 SEX collector mixture showed synergy in terms of recovery, i.e. the combined effect was much greater than would have been expected from a weighted sum of each individual contribution. It has been proposed that this may be due to the heterogeneity of the surfaces, viz. the stronger collector adsorbing onto the coarser size fraction and weaker, possibly more selective collectors adsorbing onto a finer particle fraction. Once again, a mixture of SEDTP and a frother improved the flotation recovery synergistically, which is not observed when SEX is combined with a frother. Surfactant type, size and structure all contribute to the strength of the surfactant at the airwater interface. However, variable frother types (alcohols and PPG’s) at different molecular weights all displayed a similar synergistic effect with SEDTP. Furthermore, the mineral specificity of this synergistic phenomenon was tested on a second mineral, galena. The galena responded similarly to pyrite, in that an SEDTP-frother mixture significantly improved flotation rate and recovery above any single reagent. The findings in the thesis indicate that SEDTP plays a surfactant role as indicated by its ability to reduce surface tension and improve foam stability. However the presence of solids reduced this effect. In microflotation experiments, SEDTP displayed a synergistic effect when combined with a frother, therefore indicating that it also plays a collecting role by adsorbing at the solid-water interface. This synergistic effect between SEDTP and a frother can be explained by the ability of SEDTP, as well as the frothers, to adsorb at both the air-water interface and the solid-water interface. Furthermore, the presence of one of these surfactants at an interface improves the adsorption of the other in order to maintain electroneutrality. It is proposed that these observations provide supporting evidence for the classical Leja-Schulman penetration theory on the respective role of frothers and collectors in flotation. This theory proposes that during bubble-particle attachment, these interfaces come into contact with one another and condense to form a new mixed collector-frother monolayer at the bubble-particle film. The combination of surfactants that have bubble stabilizing ability and increase particle hydrophobicity at the bubble-particle interface will ultimately improve the flotation of the particles. However, it was shown in this dissertation, that this synergistic interaction is significant only in the case of SEDTP. SEX showed no evidence of this mechanism operating at all. This may be because all available xanthate molecules are adsorbed onto the solid surface and are unavailable to act at the airwater interface. In addition, it was shown that SEX is an extremely poor surfactant at the airwater interface. These findings have important ramifications for the current processing of PGMs and BMS where DTP is widely used.